Activation of NLRP3 Is Required for a Functional and Beneficial Microglia Response after Brain Trauma - Ana Belen Lopez-Rodriguez; Céline Decouty-Perez; Victor Farré-Alins; Alejandra Palomino-Antolín; Paloma Narros-Fernández; Javier Egea (MDPI AG, 2022)
Despite the numerous research studies on traumatic brain injury (TBI), many physiopathologic mechanisms remain unknown. TBI is a complex process, in which neuroinflammation and glial cells play an important role in exerting a functional immune and damage-repair response. The activation of the NLRP3 inflammasome is one of the first steps to initiate neuroinflammation and so its regulation is essential. Using a closed-head injury model and a pharmacological (MCC950; 3 mg/kg, pre- and post-injury) and genetical approach (NLRP3 knockout (KO) mice), we defined the transcriptional and behavioral profiles 24 h after TBI. Wild-type (WT) mice showed a strong pro-inflammatory response, with increased expression of inflammasome components, microglia and astrocytes markers, and cytokines. There was no difference in the IL1β production between WT and KO, nor compensatory mechanisms of other inflammasomes. However, some microglia and astrocyte markers were overexpressed in KO mice, resulting in an exacerbated cytokine expression. Pretreatment with MCC950 replicated the behavioral and blood-brain barrier results observed in KO mice and its administration 1 h after the lesion improved the damage. These findings highlight the importance of NLRP3 time-dependent activation and its role in the fine regulation of glial response.